Optimization of Fermentation Time Enhances the Antioxidant and Antiinflammatory Activities of Tea Kombucha Cascara from Pagar Alam Robusta Coffee (Coffea canephora) - Lina Elfita; Hendri Adrat; Fathul Majidi; Fadhlika Putri Vihanda; Aulia Amira; Zulaila Hunafa; Eka Putri (Pharmacy Department, Faculty of Health Sciences, UIN Syarif Hidayatullah Jakarta, Indonesia, 2026)
https://docs.google.com/document/d/1ia1-repmtPyigOvKg4lqXogtL4Rl0h1P/edit?usp=sharing&ouid=117864675563898028088&rtpof=true&sd=true